Effect of gel-forming gums on the intestinal unstirred layer and sugar transport in vitro. Issue 5 (May 1981) - Johnson, I T; Gee, J M
Abstract : The effect of two gel-forming polysaccharide gums, guar gum and Na-carboxymethyl-cellulose (CMC), on glucose transport in vitro was investigated using everted sacs of rat jejunum. The gums were added to the mucosal bathing media to give apparent viscosities in the range of 1-110 Pascal seconds X 10(-3), mPa.s(cP). Serosal glucose transport fell steeply by about 60% as the viscosities of the mucosal media rose to 20mPa.s, and levelled off thereafter. A similar effect was observed in sacs preincubated with guar gum (15 minutes) and exposed to glucose in a subsequent guar-free incubation. Glucose transport with and without the addition of guar gum was found to be sensitive to mucosal stirring, so that, when shaken at 130 oscillations per minute, sacs exposed to guar gum (0.25 %, viscosity c.a. 16 mPa.s (cP) transported glucose at a similar rate to sacs incubated without guar at 80 oscillations per minute. By measuring the time course for the establishment of osmotic induced potentials, it was shown that incubation with guar or CMC led to an increase in the apparent thickness of the unstirred fluid layer overlying the mucosa (guar-free thickness = 317 +/- 15 mu, guar treated thickness = 468 +/- 25 mu). It is suggested that the presence of a polysaccharide gum in the fluid film surrounding the villi increases its viscosity, and thus gives rise to a thickening of the rate-limiting unstirred layer. If such an effect occurs in vivo, this could contribute to the diminished post-prandial glycaemia observed in human subjects fed guar gum.